Influencing Factors, Energy Consumption, and Carbon Emission of Central Heating in China: A Supply Chain Perspective - Liu, Guixian; Kong, Zhaoyang; Dong, Jiajia; Dong, Xiucheng; Jiang, Qingzhe; Wang, Ke; Li, Jiaman; Li, Chade; Wan, Xin (Frontiers in Energy Research, 2021)
The rapid growth of energy demand in China's central heating sector and the large differences in regions have posed challenges to its energy supply safety, which affected the progress of China's energy transformation. From a supply chain perspective, this study uses the feasible generalized least squares method to conduct empirical research on the central heating data of 17 provinces in China from 2006 to 2017. The results shows that the main factors of central heating includes energy consumption structure, heat generation method, heat transport carrier, heating degree days and heating area; The main factor that increases the energy consumption of central heating in each province is the same, namely HA. However, the main factors that reduce energy consumption in each province are different; using gas instead of coal for clean heating can reduce some greenhouse gas emissions while bringing huge gas supply pressure. According to the results, this study provides some policy suggestions.